Повышение качества обработки изображений зон износа в системах поддержания работоспособности инструментов - Деревянченко, А. Г.; Бабилунга, О. Ю.; Криницын, Д. А.; Вахромеев, И. В. (НТУ "ХПІ", 2009)
Quality improvement of cutting tool wear zones images processing in systems for their working efficiency maintenance. Methods of quality improvement of cutting tool wear zones images processing in systems for their working efficiency maintenance are considere.
Keywords: режущие инструменты; задние поверхности резца; выделение контуров; макродефект